New energy power system inertia weak position evaluation and frequency monitoring positioning - Liu, Jiaji; Di, Peng (Frontiers in Energy Research, 2024)
The high proportion of new energy into the power grid leads to a significant uneven distribution trend of the inertia of the power grid, which seriously affects the safe and stable operation of the power grid. It is urgent to carry out the inertia evaluation of the new energy power system. In view of the insufficient accuracy of the equivalent inertia evaluation method of a single inertia center in evaluating large-scale power systems, this paper first proposed the equivalent inertia evaluation method of new energy power system in the region, and proposed the evaluation index of network area inertia to reveal the weak inertia network area. Secondly, for the inertia evaluation of new energy power system nodes, monitoring devices should be installed at each bus node. As the system construction cost is too high, a node inertia evaluation model of new energy power system is established to reduce the number of monitoring devices installed. Finally, in view of the unclear basis and inaccurate location of the frequency monitoring node selection model in the evaluation of equivalent inertia, a correlation model of equivalent inertia and node inertia is established to characterize the correlation between any node inertia and system equivalent inertia in the system. The consistency of the position of the equivalent inertia evaluation frequency monitoring node and the maximum inertia node of the system was derived, and the accuracy of the maximum inertia node as a frequency monitoring node was verified by the inertia center method and the frequency center method.